Autoethnographies of Reading as an Occupation - Catherine Candler; Randa Mikeska; Kendall Lacy; Nancy Elliott; Audrey Huddleston (Scholarworks @ WMU, 2021)
Background: The conceptualization of reading as an occupation is an emerging area, and guides for occupational focus in reading intervention are incompletely formed. We explored our own experiences with reading and awareness of reading as a personal occupation for perspectives to inform our practice. Methods: We used autoethnography to capture our five separate experiences. These experiences were analyzed collectively for themes using the lens of occupation as framed by the model of occupational adaptation. Results: Across our experiences, occupational patterns, products, and meaning were identified. Themes in patterns of reading highlighted the challenges of the academic setting and the importance of time to reading activities. Products of reading were external, such as achievement and skill, and internal, such as positive and negative emotions and perceptions of limitations. The meaning of reading revolved primarily around emotional responses, how reading made the reader feel about the activity and about themselves, and the amount of effort required and for what benefit. Conclusions: Our reflexive examination of reading from an occupational perspective yielded key points for development of occupational approaches to reading intervention in our personal practices.